MENINGKATKAN CARA BERPIKIR KRITIS SISWA MELALUI STRATEGI EMBELAJARAN BERBASIS PROBLEM BASED LEARNING (PBL) DI MA NURUL IMAM - Abdul Hannan; Pudhak Prasetiyorini; Febrina Gerhani (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to determine how the implementation of Problem Based Learning (PBL) learning strategies improves students' critical thinking skills at MA Nurul Imam, identify differences in critical thinking skills before and after the implementation of PBL, and analyze factors that influence the success and failure of implementing the strategy. The study used a descriptive qualitative approach with data collection techniques through interviews, observations, and learning documentation. The results showed that the implementation of PBL at MA Nurul Imam was quite effective, providing a more active learning atmosphere and encouraging students to participate in solving problems critically. There was a significant increase in students' critical thinking skills after the implementation of the PBL strategy, which was seen from students' ability to identify problems, analyze information, and compile and communicate solutions systematically. Factors for the success of PBL implementation include teacher readiness, relevance of learning problems, and active student involvement. On the other hand, the obstacles faced include limited facilities, a learning culture that still relies on memorization, and limited learning time. This study recommends strengthening teacher training, improving learning facilities, and supporting school policies to optimize the use of PBL as an effective learning strategy in shaping students' critical thinking skills according to the demands of 21st century education.